Estimates of genetic parameters for growth traits in Dorper crossbred sheep population - Besufkad, S.; Goshme, S.; Abebe, A.; Bisrat, A.; Getachew, Tesfaye; Zewdie, T.; Lemma, S.; Areaya, A.; Gizaw, Solomon (Springer, 2024)
The study was carried out to estimate genetic and phenotypic parameters for growth traits in Dorper crossbred sheep. The data set consisted of 5717 growth records from 1347 individuals of Dorper 50% crossbred sheep descended from 43 sires and 344 dams born between the years 2012 and 2022 at Debre Birhan Agricultural Research Center sheep research station, Ethiopia. Studied traits were birth weight (WT0), weaning weight (WT3), six months weight (WT6), yearling weight (WT12), average daily gain from birth to weaning (ADG1), average daily gain from weaning to six months (ADG2), average daily gain from six months to yearling (ADG3). The (co)variance components were estimated by fitting six different univariate animal models using Average Information Restricted Maximum Likelihood (AI-REML) procedure. Contrary to the genetic trend, phenotypic performance for all studied traits showed a declining trend over the years. Direct heritability estimates of 0.10 ± 0.06, 0.29 ± 0.09, 0.37 ± 0.10, 0.10 ± 0.09, 0.43 ± 0.15, 0.04 ± 0.05, and 0.14 ± 0.09 were obtained for WT0, WT3, WT6, WT12, ADG1, ADG2 and ADG3, respectively. Genetic correlations among the studied traits ranged from -0.43 (between ADG2 and ADG3) to 0.99 (between WT3 and ADG1). Selection for weaning, six months and pre-weaning average daily gain would be expected to yield good response as these traits were found moderately heritable. Strong to moderate genetic correlation of WT3 with WT6, WT12, and ADG1 suggested that selection based on WT3 would result in improvement of other growth traits due to correlated response.